Eksplorasi Etnomatematika Pada Gedung ANRI (Arsip Nasional Republik Indonesia) Jakarta Barat: EKSPLORASI ETNOMATEMATIKA PADA GEDUNG ANRI (ARSIP NASIONAL REPUBLIK INDONESIA) JAKARTA BARAT - adrian, Muhammad; Buhairi, Fathan; Muhammad Fadhillah (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2024)
Mathematics and culture have a strong relationship in life. In Indonesia, culture is different from local wisdom, and the culture of certain community groups or tribes that support mathematical activities is called ethnomathematics. One example is cultural heritage buildings, such as the ANRI (National Archives of the Republic of Indonesia) building which was founded in 1750 in DKI Jakarta Province, precisely on Jalan Gajah Mada, West Jakarta. The purpose of the research that we use, which is exploratory with this ethnographic method, is to find and categorize the mathematical concepts contained in the ANRI building which is one of the sources of learning mathematics and efforts to develop ethnomathematics as a basis for mathematics learning. This study focuses on understanding the informal mathematical knowledge acquired by local people from their environment and culture, especially those related to cultural heritage sites, which are referred to as ethnomathematics. The study findings show that the National Archives Building is a significant cultural heritage site with historical and architectural significance. The architectural features of the building, such as the rectangular and trapezoidal shapes of the main structure and roof, reflect various geometric concepts. Overall, this research emphasizes the importance of preserving cultural heritage and documents in the National Archives to retain the historical knowledge contained within. Ethnomathematics provides a valuable framework to explore and appreciate mathematical concepts embedded in cultural artifacts, promoting a deeper understanding of mathematics through real-world activities and cultural practices.